Vitreous Substitutes: Old and New Materials in Vitreoretinal Surgery - Camilla Alovisi; Claudio Panico; Ugo de Sanctis; Chiara M. Eandi (Journal of Ophthalmology)
Recent developments in vitreoretinal surgery have increased the need for suitable vitreous substitutes. A successful substitute should maintain all the physical and biochemical properties of the original vitreous, be easy to manipulate, and be long lasting. Substitutes can be gaseous or liquid, both of which have associated advantages and disadvantages related to their physical properties and use. Furthermore, new surgical techniques with smaller vitreoretinal instruments have driven the use of more viscous substitutes. In this review, we analyze and discuss the most frequently used vitreous substitutes and look ahead to future alternatives. We classify these compounds based on their composition and structure, discuss their clinical use with respect to their associated advantages and disadvantages, and analyze how new vitreoretinal surgical techniques have modified their use.